Developing Mufrodat Asik Snakes-And-Ladders (Utama) Media For Arabic Language Learning In Class V At MI Bahrul Ulum Kemlagilor - Nurusshofa, Moh Farih; Fithriyah, Saadah; Viyanti, Pratiwi (Program Studi Pendidikan Agama Islam (PAI), 2024)
The present study aimed to address the problems encountered in Arabic learning for fifth-grade students at MI Bahrul Ulum, specifically the lack of innovative media, with a particular focus on Mufrodat materials. In addition, students' disinterest in learning Arabic can be attributed to the fact that teachers rely solely on traditional learning resources, such as textbooks devoid of any innovative media. This results in students experiencing boredom and lack of concentration during lessons, which renders learning uninteresting and repetitive. In addition to determining the degree of interest in Mufrodat Asik Snakes-and-Ladders (UTAMA) media under development, this study was focused on providing a description of the procedure used in its creation. To achieve this aim, the ADDIE model was employed by the following five stages: analysis, design, development, implementation, and evaluation. The findings of the study indicate that the Mufrodat Asik Snakes-and-Ladders (UTAMA) media product underwent a methodical development process. Several stages of validation were completed to ensure the media were valid and suitable. Media experts assessed the product with a 94% (very valid) rating, followed by language experts with a 95% (very valid) rating, and material experts with a 98% (very valid) rating. In the interim, students evaluated the attractiveness of the media through a series of testing phases and responses to a questionnaire: 97% for individual trials, 99% for small group trials, and 95% for large group trials (all piqued interest). Thus, it can be concluded that the developed Mufrodat Asik Snakes-and-Ladders (UTAMA) media satisfies the criteria for attractiveness and validity/feasibility, and can be utilized for educational purposes.